2023
DOI: 10.1007/s00586-023-07997-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel classification that defines the normal cervical spine: an analysis based on 632 asymptomatic Chinese volunteers

Zixiao Zhang,
Jinyu Wang,
Rile Ge
et al.

Abstract: Purpose The “normal” cervical spine may be non-lordotic shapes and the cervical spine alignment targets are less well established. So, the study was to propose novel classification for cervical spine morphologies with Chinese asymptomatic subjects, and to address cervical balance status based on the classification. Method An overall 632 asymptomatic individuals on cervical spine were selected from January 2020 to December 2022, with six age groups from 20–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Importantly, the development of decreased cervical lordosis has been associated with exacerbation of the Neck Disability Index (NDI) and Visual Analogue Scale (VAS) for neck pain [ 26 ]. However, a previous study of spinal alignment in asymptomatic volunteers has reported that optimal cervical spine alignment varies with age [ 27 ]. For example, the normal range of cervical lordosis is 16 ± 16° for women in their 30s and 25 ± 16° for those in their 60s [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the development of decreased cervical lordosis has been associated with exacerbation of the Neck Disability Index (NDI) and Visual Analogue Scale (VAS) for neck pain [ 26 ]. However, a previous study of spinal alignment in asymptomatic volunteers has reported that optimal cervical spine alignment varies with age [ 27 ]. For example, the normal range of cervical lordosis is 16 ± 16° for women in their 30s and 25 ± 16° for those in their 60s [ 28 ].…”
Section: Discussionmentioning
confidence: 99%